AKTA PEMBAGIAN HAK BERSAMA YANG DIBUAT NOTARIS BERDASARKAN SURAT KETERANGAN WARIS PALSU ATAU DIPALSUKAN (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 688 K/PID/2017) - Adit Wiratama; Sugandi Ishak (Jurnal Hukum Adigama, 2020)
Legal Heirs Certificate (SKW) is a letter that aims to determine someone to be an heir, but in practice many are faked. The problems faced in writing this thesis are how the legal consequences of the Deed With Rights Allocation (APHB) made by a Notary based on a forged Inheritance Certificate (SKW), a case study of the Supreme Court Decision Number 688K/Pid/2017. The research method used in writing this thesis is normative legal research. The results showed that the PPAT's negligence or deliberate action in making the deed would result in the deed being degraded as a strong means of evidence in the future which could have turned the deed into an underhand deed. Intentionally in making SKW registered by the village head / village head and sub-district head as contained in the Supreme Court Decision Number 688K/Pid/2017 in making a legally flawed deed (APHB) may result in the deed being null and void, because subjective requirements are not fulfilled (agreement of both parties) which has legal implications that the certificate of inheritance can be canceled. In carrying out his position, it is appropriate for the Notary to hold and carry out his position in accordance with the applicable law (on the track), which regulates the powers, obligations and prohibitions in making deeds as confirmed in Law Number 2 of 2014 concerning Amendments to the Law. Number 30 of 2004 concerning the Position of Notary Public